UJI AKTIVITAS ANTIOKSIDAN HASIL DEGRADASI LIGNIN DARI SERBUK GERGAJI KAYU KALBA (Albizia falcataria) DENGAN METODE TBA (Thio Barbituric Acid) - Undri Rastuti; Purwati Purwati (Universitas Jenderal Soedirman, 2010)
Antioxidants are compounds that can delay, retard or inhibit the oxidation reaction. Lignin is a natural polymer consisting of monomeric substituted phenols. Wood lignin degradation Kalba (Albizia falcataria) yields substituted phenol. The purpose of this study was to test the antioxidant activity of compounds of lignin degradation products Kalba using TBA (Thiobarbituric Acid). Wood lignin degradation products Kalba tested antioxidant activity using the TBA method. Phase test phase of this antioxidant activity is sample preparation, determination of the maximum wavelength, determination of equilibrium time, absorbance measurements and determination of the percentage of inhibition. The wavelength maximum for BHT test solution was obtained at 530 nm. The stability of absorbance achieved after 80 minutes equilibrium time. BHT test solution and sample solution containing the degradation of lignin 0.10% (w/v) increased but not as sharp as the absorbance of control, this suggests that the degradation of wood lignin Kalba have activity as an antioxidant, which relative minimize 13,70 % compare with BHT.